Western representations of childhood and the quest for a spiritual social work practice - Oak, Eileen (Socialno delo, 2018)
The article examines the social constructions of childhood in the West over the past century, to illustrate how they stem from adult-centric perspectives and how they continue to shape policy initiatives about children's rights and welfare. Such perspectives are underpinned by discourses which pre-date the Enlightenment era and continue to have implications for generating child-centred, welfare policies and practice. It will explore these discourses in the context of the 1989 UN Convention on the Rights of the Child (UNCORC), and various social policies to address child abuse. This is to contend that, without a new sociology of childhood approach underpinning these policies, they will continue to fail to address children's welfare and protection needs, and be implicated in their continued marginalisation. In making this assertion, it argues for a more holistic model of childhood, characterised by the new sociology of childhood combined with a form of secular humanism. Such a synthesis of ideas can offer a more empowering child protection praxis, one which promotes children's agency and "childhood" as an autonomous stage in the life-cycle.
Keywords: duhovnost; Konvencija o otrokovih pravicah; posvetni humanizem; socialna politika; sociologija otroštva; zaščita otrok